Scientific production on the applicability of phenytoin in wound healing - Flávia Firmino; Alessandra Maria Pereira de Almeida; Rita de Jesus Grijó e Silva; Graziela da Silva Alves; Daniel da Silva Grandeiro; Lúcia Helena Garcia Penna (SciELO, 2014)
Phenytoin is an anticonvulsant that has been used in wound healing. The objectives of this study were to describe how the scientific production presents the use ofphenytoinas a healing agent and to discuss its applicability in wounds. A literature review and hierarchy analysis of evidence-based practices was performed. Eighteen articles were analyzed that tested the intervention in wounds such as leprosy ulcers, leg ulcers, diabetic foot ulcers, pressure ulcers, trophic ulcers, war wounds, burns, preparation of recipient graft area, radiodermatitis and post-extraction of melanocytic nevi. Systemic use ofphenytoinin the treatment of fistulas and the hypothesis of topical use in the treatment of vitiligo were found. In conclusion, topical use ofphenytoinis scientifically evidenced. However robust research is needed that supports a protocol for the use ofphenytoinas another option of a healing agent in clinical practice.